A Retrospective Analysis of Development of the National Oil Processing Complex - Rudyka Viktor I. (Bìznes Inform, 2017)
The article provides a retrospective analysis of development of the national oil processing complex, which enabled the author to conclude about its decline both in the resource and the production as well as in the infrastructural components. However, this type of industry has to be driven by the world trends, which increase its uncompetitiveness towards the foreign counterparts. Ukraine does not take advantage of the global oil market, but is forced to adapt to the demands of individual exporting countries.